2021
DOI: 10.26434/chemrxiv-2021-b2d13
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-Component, Photocatalytic H2 Production Through Acceptorless Alcohol Dehydrogenation: Atypical Metal-Ligand Cooperativity in a Ruthenium(II)-PN/P Complex

Abstract: Metal-ligand cooperativity (MLC) involving reversible aromatization/dearomatization of pyridine-derived pincer ligands is considered important in acceptorless (de)hydrogenation for dihydrogen generation and storage. Dehydrohalogenation of pyridine-derived pincer ruthenium complexes often leads to dearomatized moieties. Thus, we were surprised to find an aromatized kappa-3-NCP binding mode in [{LutP`}Ru(CO)(H)(PPh3)] (2) upon dehydrohalogenation of the lutidine-derived PN/P complex [{LutP}Ru(CO)(Cl)(H)(PPh3)] (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We also tested Milstein’s Ru-PNN trans -dihydride 3Py and obtained TON = 1–3 with or without light, but 3Py is known to spontaneously lose H 2 on standing in solution at rt, and we found that even the chlorido precursor to 3Py (i.e., 1Py ) produces hydrogen on irradiation in anhydrous benzene; thus, the comparison is rather inconclusive . We also note that irradiation of Ru-MACHO and 3Py with broad-band light resulted in solutions containing a multitude of hydride resonances in the 1 H NMR spectrum and speciation by 31 P­{ 1 H} NMR was complicated.…”
Section: Resultsmentioning
confidence: 96%
“…We also tested Milstein’s Ru-PNN trans -dihydride 3Py and obtained TON = 1–3 with or without light, but 3Py is known to spontaneously lose H 2 on standing in solution at rt, and we found that even the chlorido precursor to 3Py (i.e., 1Py ) produces hydrogen on irradiation in anhydrous benzene; thus, the comparison is rather inconclusive . We also note that irradiation of Ru-MACHO and 3Py with broad-band light resulted in solutions containing a multitude of hydride resonances in the 1 H NMR spectrum and speciation by 31 P­{ 1 H} NMR was complicated.…”
Section: Resultsmentioning
confidence: 96%